Evaluative analysis of authentic thematic learning assessment at Indonesian Islamic primary school - Abdul Kadir; Kharis Sulaiman Hasri (Jurnal Prima Edukasia, 2021)
While several research papers on authentic assessment have been extensively explored, few have addressed the evaluation of authentic assessments starting from the stages of planning, process/implementation, and outcome. To fill the research gap, the purpose of the present case study is to investigate the authentic evaluation of thematic learning enactment. To collect the data, observations, in-depth interviews, and documentation were conducted. The results of this study indicate that the teacher's comprehension of authentic assessment is generally good. However, several assessment techniques did not work as planned. Based on this, the enactment of authentic assessment is still in the poor category. Processing and reporting resulting from the type of assessment are executed according to procedures. However, some did not follow the assessment guidelines of the elementary school level's learning outcome assessment, especially the effective one.